Factores sociales que contribuyeron al incremento de la pobreza monetaria en Loreto durante el año 2023 - Pérez Dávila de Benavente, Antonia Modeyne (2025)
This research analyzes the relationship between social factors and monetary poverty in the Loreto region during the year 2023. Using a quantitative, correlational, and non-experimental design, a logistic regression model was applied to estimate the influence of perceived insecurity, institutional trust, formal employment, and education on the probability of a household being poor. The results show that perceived insecurity has a negative relationship with poverty, suggesting that higher-income households may report greater insecurity due to their location in more economically dynamic urban areas. On the other hand, trust in institutions is positively associated with poverty, possibly reflecting a dependence of vulnerable households on social assistance programs. Formal employment emerges as the most significant factor in reducing poverty, followed by education, although the latter has a smaller impact. These findings highlight the importance of promoting job formalization, improving educational quality, and designing social policies that encourage economic self-sufficiency. Public policy recommendations are proposed to strengthen access to stable employment and sustainably reduce poverty in the region.